2022
DOI: 10.1038/s41598-022-24172-y
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-modified phosphate-based glass micro-filler improves Candida albicans resistance of auto-polymerized acrylic resin without altering mechanical performance

Abstract: Colonization of auto-polymerized acrylic resin by pathogenic Candida albicans is a common problem for denture users. In this study, zinc-modified phosphate-based glass was introduced into an auto-polymerized acrylic resin at concentrations of 3, 5, and 7 wt.%. The mechanical or physical properties (flexural strength, elastic modulus, microhardness, and contact angle), surface morphology of the resultant materials, and the antimicrobial effect on C. albicans were investigated. There were no statistical differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…However, the OD value of S. mutans decreased with increasing Sr-PBG content in the composite resin. These results are similar to those obtained with silver-, zinc-, and gallium-doped bioactive glass additives 25 , 37 , 38 . Strontium is a major mineral that acts as an antimicrobial agent against S. mutans 20 .…”
Section: Discussionsupporting
confidence: 88%
“…However, the OD value of S. mutans decreased with increasing Sr-PBG content in the composite resin. These results are similar to those obtained with silver-, zinc-, and gallium-doped bioactive glass additives 25 , 37 , 38 . Strontium is a major mineral that acts as an antimicrobial agent against S. mutans 20 .…”
Section: Discussionsupporting
confidence: 88%
“… 32 NMBG was applied in the compounding of organic materials to enhance their properties. 33 , 34 Studies have once shown that NMBG scaffolds can support cell adhesion, proliferation, and differentiation in vitro. When in contact with body fluids in vivo, NMBG slowly released internally loaded drugs, further enhancing its biological activity.…”
Section: Resultsmentioning
confidence: 99%
“…Antibacterial properties can also be obtained by the addition of, e.g., AgVO 3 [ 14 ], mesoporous silica nanoparticles [ 28 ], zinc-modified phosphate-based glass microfiller [ 29 ], and ZnO [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…If the amount of unsilanized glass added is increased, a decrease in flexural strength can be observed [ 29 ]. For this reason, the measurable benefit of using half of the glass in the silanized form is the improvement of the mechanical properties of the new sample (Agarwal) [ 35 ].…”
Section: Discussionmentioning
confidence: 99%